Physico-chemical and microbiological changes in commercial tilapia (Oreochromis niloticus) during cold storage - GUTIÉRREZ GÚZMAN, Nelson; FERNÁNDEZ SEGOVIA, Isabel; FUENTES LÓPEZ, Ana; RUIZ RICO, Maria; BARAT BAVIERA, José Manuel (Vitae, 2015)
Background: The microbiological and chemical processes are the main responsible for deterioration of fresh fish. Therefore, it is essential to avoid these processes by applying good manufacturing practices during fish handling, distribution and storage. Objective: The aim of this paper was to evaluate the physico-chemical and microbial changes in commercial tilapia (Oreochromis niloticus) during cold storage in order to establish the shelf life since its arrival at the supermarket. Methods: 27 aquacultured tilapia specimens were analyzed at 0, 2, 4, and 7 days of storage at 4ºC. Measurements of texture, color, water holding capacity, total volatile basic nitrogen (TVB-N), thiobarbituric acid index, ATP-related compounds, as well as microbial analyses were carried out. Results: The TVB-N content was high at the beginning of the study, remaining stable during the storage. Lipid oxidation of samples was minimum, so this process did not contribute to the fish spoilage. It was observed the breakdown of inosine-5’- monophosphate (IMP) into Ino (inosine), and Ino into Hx (hypoxantine). The texture parameters and colour underwent changes as a consequence of the fish spoilage. Low microbial counts were observed at day 0, but Enterobacteriaceae and mesophilic counts gradually increased throughout storage. Conclusions: The K1-value showed the progressive spoilage of the fish during the cold storage. The decrease of hardness and firmness confirmed the loss of quality throughout the time of study. The low microbial counts at the beginning of the study demonstrated the good quality of the tilapia; however, the increase of the mesophilic counts at the end of the studied period showed that tilapia was not fit for human consumption at day 7.